Mineralocorticoid receptor antagonists use in patients with heart failure and impaired renal function. - Anna Jonsson Holmdahl; Helena Norberg; Fredrik Valham; Ellinor Bergdahl; Krister Lindmark (PLoS ONE, 2021)
Aims Impaired renal function is a major contributor to the low proportion of mineralocorticoid receptor antagonist (MRA) treatment in patients with heart failure with reduced ejection fraction (HFrEF). Our aims were to investigate the impact of MRA treatment on all-cause mortality and worsening renal function (WRF) in patients with HFrEF and moderately impaired renal function. Methods Retrospective data between 2010-2018 on HFrEF patients from a single-centre hospital with estimated glomerular renal function (eGFR) < 60 ml/min/1.73 m2 were analysed. WRF was defined as a decline of by eGFR ≥ 20%. Results 416 patients were included, 131 patients on MRA and 285 without MRA, mean age was 77 years (SD ± 9) and 82 years (SD ± 9), respectively. Median follow-up was 2 years. 128 patients (32%) experienced WRF, 25% in the MRA group and 30% in patients without MRA (p = 0.293). In multivariable analysis, hospitalization for heart failure and systolic blood pressure were associated with WRF (p = 0.015 and p = <0.001), but not use of MRA (p = 0.421). MRA treatment had no impact on the risk of adjusted all-cause mortality (HR 0.93; 95% CI, 0.66-1.32 p = 0.685). WRF was associated with increased adjusted risk of all-cause mortality (HR 1.43; 95% CI, 1.07-1.89 p = 0.014). Use of MRA did not increase the adjusted overall risk of mortality even when experiencing WRF (HR 1.15; 95% CI, 0.81-1.63 p = 0.422). Conclusion In this cohort of elderly HFrEF patients with moderately impaired renal function, MRA did not increase risk for WRF or all-cause mortality.